Combination treatment of metformin and red fruit (Pandanus conoideus l.) extract increased pancreatic β cell density but had no effect toward fasting blood glucose and glycated albumin levels in diabetic male wistar rats (Rattus norvegicus) - Ingrid Rotinsulu; Wimpie I. Pangkahila; A.A. Gede Budhiarta (Fakultas Kedokteran Universitas Udayana, 2019)
Background: Diabetes mellitus (DM) is a degenerative disease associated with premature aging characterized by hyperglycemia. Hyperglycemia in people with DM causes oxidative stress and increases Glycated Albumin level, which is the initial precursor to the formation of AGEs. In turn, AGEs will lead to pancreatic β cell damage and apoptosis. Red fruit (Pandanus conoideus L) contains phytochemicals with antioxidant that has the potential to reduce diabetic complications. Therefore, this study aimed to evaluate the effect of metformin and red fruit extract combination toward blood glucose, glycated albumin and pancreatic β cells density in diabetic rats (Rattus norvegicus). Methods: A post-test only control group study was conducted using 36 male Wistar rats as subject. All subjects were induced for type-2 DM with Streptozotocin and Nicotinamide. The diabetic rats were then divided into 2 groups: the positive control group treated with metformin + placebo and the treatment group treated with metformin + red fruit extract. Pancreatic β cell, fasting blood glucose and glycated albumin assessments were performed after 21 days of treatment. Results: The results showed the mean number of pancreatic β cells in the treatment group was higher than the control group (116.11±33.14 vs 83.20±23.94 cells/visual field; p=0.002). But the mean fasting blood glucose in the treatment group was not significantly different compared to the control group (107.67±14.93 vs. 113.67±11.19 mg/dl; p=0.181). The same result also found in the gycated albumin level (Treatment vs control: 6.97±3.63 vs 6.42±4.01 ng/ml; p=0.666). Conclusion: It can be concluded that the administration of red fruit extract increased the density of pancreatic β cell but did not reduce fasting blood glucose and glycated albumin levels in diabetic Wistar rats.